Decoding your destiny. - Seah, Kai Ling. (2012)
The premise of this project exploration is to analyze the traditional Chinese Culture of Physiognomy and how we can use modern graphics to re-present old beliefs and superstitions into a tangible asset that is easily accessible for the younger generation. This project seeks to investigate how we can use Physiognomy as a method to identify nonverbal signals, and cues of others to create our interest and investment in them. This will be done based on the existing theories of face reading in the expression of face shapes, and physical features of our face. This project, in attempt to re-establish the link between how our character can be determined by our facial features, will be developed through the use of visual toolkit.